Measurement of $ψ(2S)$ polarisation in $pp$ collisions at $\sqrt{s}=7$ TeV - collaboration, L; Aaij, R; Adeva, B; Adinolfi, M; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Ali, S; Alkhazov, G; Cartelle, P; et al. (Springer New York LLC, 2014)
The polarisation of prompt $ψ(2S)$ mesons is measured by performing an angular analysis of $ψ(2S)→ μ^{+} μ^{-}$ decays using proton-proton collision data, corresponding to an integrated luminosity of 1.0 fb$^{-1}$, collected by the LHCb detector at a centre-of-mass energy of 7 TeV. The polarisation is measured in bins of transverse momentum $p_T$ and rapidity $y$ in the kinematic region $3.5